2021
DOI: 10.1101/2021.01.18.427192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sodium channel Nav1.2-L1342P variant displaying complex biophysical properties renders hyperexcitability of cortical neurons derived from human iPSCs

Abstract: With the wide adoption of whole-exome sequencing in children having seizures, an increasing number of SCN2A variants has been revealed as possible genetic causes of epilepsy. Voltage-gated sodium channel Nav1.2, encoded by gene SCN2A, is strongly expressed in the pyramidal excitatory neurons and supports action potential firing. One recurrent SCN2A variant is L1342P, which was identified in multiple patients with early-onset encephalopathy and intractable seizures. Our biophysical analysis and computational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
(187 reference statements)
1
5
0
Order By: Relevance
“…The major finding from this line was an enhancement of the action potential waveform, similar to a human neuronal model of the SCN2A-L1342P variant (Que et al, 2021). However, the L1342P variant is gain-of-function from computational modelling and its association with epilepsy, but it has mixed gain-and loss-of-function phenotypes (Begemann et al, 2019;Que et al, 2021). Even with action potential waveform enhancements, we did not observe increases in neuronal excitability, dissimilar to the L1342P variant.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The major finding from this line was an enhancement of the action potential waveform, similar to a human neuronal model of the SCN2A-L1342P variant (Que et al, 2021). However, the L1342P variant is gain-of-function from computational modelling and its association with epilepsy, but it has mixed gain-and loss-of-function phenotypes (Begemann et al, 2019;Que et al, 2021). Even with action potential waveform enhancements, we did not observe increases in neuronal excitability, dissimilar to the L1342P variant.…”
Section: Discussionsupporting
confidence: 65%
“…The G1744* variant is loss-of-function but the individual presents with early-onset seizures, and the variant is past the predicted non-sense mediated decay breakpoint (Nagy and Maquat, 1998;Sanders et al, 2018). The major finding from this line was an enhancement of the action potential waveform, similar to a human neuronal model of the SCN2A-L1342P variant (Que et al, 2021). However, the L1342P variant is gain-of-function from computational modelling and its association with epilepsy, but it has mixed gain-and loss-of-function phenotypes (Begemann et al, 2019;Que et al, 2021).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Recent studies have reported similar hyperexcitable neurons that carry ASD-and epilepsy-related mutations for SCN2A (Sodium channel protein type 2 subunit alpha) (67,68). Both epilepsy and ASD are also reported in patients with PRICKLE2 mutations (26,27), while Prickle2 knockout mice display a lower threshold for seizures (26) and ASD-like behaviors (27).…”
Section: Prickle2 Function In Asd and Epilepsymentioning
confidence: 97%